Soil bacteriome diversity and composition of rooftop and surface gardens in urban and peri-urban areas of Bangladesh - Rana, Md. Liton; Hoque, M. Nazmul; Rahman, M. Shaminur; Kumar Pramanik, Pritom; Islam, Md. Saiful; Punom, Sadia Afrin; Ramasamy, Srinivasan; Schreinemachers, Pepijn; Oliva, Ricardo; Rahman, Md. Tanvir (Springer, 2024)
Soil microbiome science, rapidly evolving, predominantly focuses on field crop soils. However, understanding garden soil microbiomes is essential for enhancing food production sustainability in garden environments. This study aimed to unveil the bacteriome diversity and composition in rooftop garden soils (RGS) and surface garden soils (SGS) across urban (Dhaka North and Dhaka South City Corporations) and peri-urban (Gazipur City Corporation) areas of Dhaka Division, Bangladesh. We analyzed 11 samples, including six RGS and five SGS samples from 11 individual gardens using 16S rRNA (V3–V4 region) gene-based amplicon sequencing. A total of 977 operational taxonomic units (OTUs), including 270 and 707 in RGS and SGS samples, respectively, were identified. The observed OTUs were represented by 21 phyla, 45 classes, 84 orders, 173 families, and 293 genera of bacteria. Alpha diversity indices revealed significantly higher bacterial diversity in SGS samples (p = 0.01), while beta diversity analyses indicated distinct bacteriome compositions between RGS and SGS samples (p = 0.028, PERMANOVA). Despite substantial taxonomic variability between sample categories, there was also a considerable presence of shared bacterial taxa. At the phylum level, Bacilliota (61.14%), Pseudomonadota (23.42%), Actinobacteria (6.33%), and Bacteroidota (3.32%) were the predominant bacterial phyla (comprising > 94.0% of the total abundances) in both types of garden soil samples. Of the identified genera, Bacillus (69.73%) and Brevibacillus (18.81%) in RGS and Bacillus (19.22%), Methylophaga (19.21%), Acinetobacter (6.27%), Corynebacterium (5.06%), Burkholderia (4.78%), Paracoccus (3.98%) and Lysobacter (2.07%) in SGS were the major bacterial genera. Importantly, we detected that 52.90% of genera were shared between RGS and SGS soil samples. Our data reveal unique and shared bacteriomes with probiotic potential in soil samples from both rooftop and surface gardens. Further studies should explore the functional roles of shared bacterial taxa in garden soils and how urban environmental factors affect microbiome composition to optimize soil health and sustainable food production.